Authoritative Parenting and Emotional Intelligence Predict Learning Independence: Pendidikan Orang Tua yang Otoritatif dan Kecerdasan Emosional Memprediksi Kemandirian Belajar - Faradiba Faradiba; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Learning independence represents a core dimension of student self-regulated learning and is widely recognized as a prerequisite for academic success in secondary education. Specific Background: Empirical observations at SMPN 2 Tanggulangin revealed that a considerable proportion of students demonstrated moderate to low levels of learning independence, reflected in discipline, responsibility, initiative, and self-confidence indicators. Authoritative parenting and emotional intelligence have been identified in developmental psychology as key contextual and internal determinants associated with adaptive academic behavior. Knowledge Gap: Previous studies have predominantly examined these variables separately, leaving limited evidence regarding their simultaneous contribution to learning independence among junior high school students. Aims: This quantitative correlational study aimed to examine the simultaneous and partial relationships of authoritative parenting and emotional intelligence with students’ learning independence. Results: Data from 227 students analyzed using multiple linear regression indicated a significant simultaneous relationship (F = 55.461, p < 0.05), with both predictors showing significant partial coefficients. Emotional intelligence demonstrated a stronger standardized coefficient (β = 0.400) than authoritative parenting (β = 0.280). The model accounted for 33.1% of the variance in learning independence. Novelty: This study integrates family parenting style and emotional intelligence within a single regression framework in the context of Indonesian junior high school students. Implications: The findings underscore the importance of structured parenting practices and emotional regulation competencies in fostering autonomous learning behaviors, informing school-based counseling programs and parent education initiatives. Highlights: Simultaneous regression analysis confirmed both predictors jointly explained 33.1% of variance in student autonomy. Emotional regulation capacity showed the strongest statistical coefficient among examined variables. Most participants were classified in the moderate category of self-directed academic behavior. Keywords:Authoritative Parenting; Emotional Intelligence; Learning Independence; Multiple Linear Regression; Junior High School Students